Pengaruh Inflasi Dan Pertumbuhan Ekonomi Terhadap Penerimaan Pajak Di Indonesia - Lely Suryani; Andini Silvia Putri Sudarsono (CV. ITTC INDONESIA, 2024)
This research aims to obtain evidence regarding the impact of inflation and economic growth on tax revenue. The study employs an associative quantitative research method using secondary data obtained from the official website of the Central Statistics Agency (BPS) for each province during the period 2018-2022. Purposive sampling method is used with criteria tailored to the research needs. The study includes samples from 14 provinces with 5 years of research so that the total of 70 observations. Hypothesis testing is conducted using Eviews 10. Data analysis results indicate that inflation and economic growth simultaneously influence tax revenue, however partially, it was found that inflation affects tax revenue, while economic growth does not